Ventilatory threshold concordance between ergoespirometry and heart rate variability in female professional cyclists - Mina-Paz, Y.; Tafur-Tascon, L. J.; Cabrera-Hernandez, M. A.; Povea-Combariza, C.; Tejada, X.; Hurtado-Gutierrez, H.; Garcia-Corzo, S. A.; Garcia-Vallejo, F. (Journal of Human Sport & Exercise, 2023)
The ventilatory threshold (VT) is the point at which ventilation intensifies disproportionately concerning to the oxygen uptake, this parameter is essential within the training methodology to optimize performance; the purpose of this work is to measure the degree of agreement between the determination of the ventilatory threshold determined by for oxygen uptake and four methods by Heart Rate Variability (HRV).